Pemanfaatan Limbah Plastik Menjadi Produk Kreatif bagi Pelajar di SDN Kalisari 1 - Zulfar, Mochamad Ilham; Devika, Sofia Cinintya; Jafar, Latifah Rukmiati Ifnu; Prayitno, Erica Diana; Rahmatin, Leily Suci (Universitas Nusantara PGRI Kediri, 2024)
The waste problem in Surabaya is exacerbated by limited land, population growth, and ineffective management, with plastic waste being one of the main contributors. The Community Service Program in Kalisari, Surabaya, aims to reduce environmental impact through education and practical plastic waste management at SDN Kalisari 1. The activities involved methods such as observation, practical processing of plastic waste, and documentation to evaluate education and the utilization of plastic waste. This program provided practical learning to the fifth-grade students of SDN Kalisari 1 on transforming plastic waste into useful and aesthetic products, such as flower pots and trash bins. The plastic waste utilization program initiated by KKN students at SDN Kalisari 1 successfully enhanced students' awareness of plastic waste management, stimulated their creativity in designing useful products, and encouraged environmentally friendly behavior, aligning with the sustainable development goals (SDGs) related to responsible consumption and production.